PULSE CODING OF FUZZY LOGIC VALUES - Semenova, Olena (Scientific Works of Vinnytsia National Technical University, 2011)
In this article methods of pulse-frequency, pulse-width and pulse-phase encoding of fuzzy logic values have been proposed. Their difference is that fuzzy logic zero values are encoded not as an absence of pulses, but as pulses with a minimum value of frequency, width or phase. That allows the methods to be used in fuzzy logic elements synthesis.